Pancreas angiosarcoma : case report of a rare cause of abdominal pain - Faria, Aldara (2021)
© 2020 The Authors. Published by Elsevier Ltd on behalf of IJS Publishing Group Ltd. This is an open access article under the CC BY-NC-ND license (http:// creativecommons.org/licenses/by-nc-nd/4.0/)